- En historisk Theodice - Vind, Ole (Grundtvig-Studier, 2015)
En historisk Theodice [A Historical Theodicy] By Ole Vind Grundtvig’s first World Chronicle from 1812 (VK 1812) is noted especially for its sharp criticism of contemporary culture. It can be read as a Lutheran revivalist sermon passing judgment on great historical as well as contemporary figures who are condemned for their lack of orthodox Christian faith. Read in the light of Grundtvig’s later works, however, the book carries the seeds of that philosophy of history which from 1832 onwards became the mainstay of all his writings. Thus, in VK 1812 are found the first traces of that original vision which in Christenhedens Syvstjerne (The Seven Sisters of Christendom, Grundtvig’s great cycle of church historical poems written 1854-55, published 1860) follows church history through seven national Churches of which the future Hindu (Christian) Church is the last. Likewise, in the chronicle are found Grundtvig’s first speculations on ethnic origins, later clarified into his idea of four principal peoples in World History (i.e. the Jews, the Greeks and the Romans in antiquity and the Scandinavians in modern times). In spite of his harsh condemnation of his contemporaries, Grundtvig concludes VK 1812 optimistically, prophesying a spiritual and Christian renewal in Scandinavia through the future university in Kristiania (i.e. Oslo) in Norway (founded 1811 and opened 1813). Such a trust in learning and scholarship was characteristic of the European age of Enlightenment with its belief in progress. In later major works, Grundtvig expressed this attitude in an original Nordic version which also formed the basis of his thoughts about education and folk high schools. In VK 1812 Grundtvig briefly characterizes the German thinkers who were the foundation of his philosophy of history. Even if they are all blamed for their lack of orthodox faith, his delineation of them is remarkably mild. Later, rather surprisingly, Grundtvig appeared to reconcile himself to a great extent with the German “naturalists imbued with spirit”. The quite positive words about those German philosophers whom he otherwise rather criticized, presage the deep inspiration in Grundtvig’s mature works particularly from Herder and Fichte. An exceptional role is played to Grundtvig by Lessing who raised the principal question of Protestant religious philosophy about the relationship between Christianity and history. Already in VK 1812, Grundtvig’s philosophy of history is also a philosophy of religion in the shape of a historical theodicy. As in his works to come, Grundtvig’s answer to Lessing’s question is thus quite the opposite of Søren Kierkegaard’s to whom Lessing, too, meant a serious philosophical challenge.